Results of analysis of epidemological indicators of viral hepatitis c in regions of the world as part of activities to improve pharmaceutical provision for patients - Nozdrina, Almira; Volkova, Alina; Cherkashyna, Alina; Ovakimian, Olga (ScienceRise: Pharmaceutical Science, 2022)
Viral hepatitis affects hundreds of millions of people worldwide, the most dangerous of which are hepatitis B and C. The aim of our study was to study the prevalence and incidence of HC in the world and in Ukraine, as well as approaches in pharmacotherapy of HC to further identify effective measures to eliminate HC and improve pharmaceutical supply to patients in HC in Ukraine. The materials of the study were WHO statistical reports, national country reports, national recommendations for pharmacotherapy, the analysis of which was carried out by methods of generalization of information, analytical, comparative method. Results of the research. According to the WHO segmentation, the most frequent cases of HC are found in the populations of the Nordic-Mediterranean region (15 million cases) and the European region (12 million cases). Four countries in the world account for more than 40 % of all people infected with HC, two of which are in the Nordic-Mediterranean region (Pakistan – 7.2 and Egypt – 5.6 million people, respectively). The incidence of HC in Western Europe is up to 0.5 %, while in Northern Europe it is up to 3.3 %. Currently, the highest number of first-time HC infections in 2019 was registered among the populations of Ireland, the United Kingdom and Finland. The lowest incidence rates were found in Romania, Italy and Greece. It has been established that males aged 20–45 years prevail among those infected with HC. It was found that the prevalence of HC in Ukraine in 2015 was 3 %, according to 2020 – 5 %, with the annual number of newly recorded cases of HC increases by at least 7 %. According to the gender distribution, the ratio is on average 1.3 patients among men to 1 patient among women. An analysis of international guidelines for the pharmacotherapy of HC has shown that their latest revisions contain new direct-acting antiviral drugs, namely combinations of drugs such as glecaprevir / pibrentasvir and sofosbuvir / velpatasvir. The standard of HC treatment in Ukraine, approved in January 2021, is more in line with the recommendations of the WHO (2018), AASLD (2019) and EASL (2020) than the 2016 treatment protocol. Conclusions. The annual rate of HC infection in the world remains very high and is estimated at 1.5 million people. Regular revision and updating of standards of HC treatment with the latest direct-acting antiviral drugs, annual increase in the number of people in the world and in Ukraine who receive timely diagnosis of HCV and its full treatment are effective steps to achieve the goal of eliminating viral hepatitis